Factors associated with the severity of neonatal subgaleal haemorrhage following vacuum assisted delivery. (February 2020) - Levin, Gabriel; Mankuta, David; Eventov-Friedman, Smadar; Ezra, Yossef; Koren, Adi; Yagel, Simcha; Rottenstreich, Amihai
Abstract: Objective: To evaluate factors associated with subgaleal hemorrhage (SGH) severity following attempted vacuum-assisted delivery (VAD). Study design: This retrospective cohort study was conducted in a tertiary medical center. The population comprised parturients who delivered at our medical center during 2009–2018, and who underwent attempted VAD with singleton pregnancies that resulted in neonatal SGH formation. SGH severity was classified as mild and non-mild (moderate or severe). The main outcome measures were determinants associated with SGH severity. Results: Among 350 neonates with SGH, the degree of severity was non-mild for 48 (13.7%). Compared to the mild group, in the non-mild group, small for gestational age was more common (8.2% vs. 2.6%, p = 0.04). Compared to the mothers in the mild group, in the non-mild group, the proportion with two or more deliveries was lower (0% vs. 7.3%, p = 0.05), gestational diabetes was more common (12.5% vs. 4.6%, p = 0.02), the rate of cervical ripening was higher (27.1% vs. 12.9%, p = 0.02), the duration of the second stage of delivery was longer (mean 177 vs. 152 min, p = 0.04), and the rate of two dislodgments was higher (31.2% vs. 15.2%, p = 0.006). On multivariate analysis, only cervical ripening (adjusted odds ratio [OR]: 2.50; 95% confidence interval [CI]: 1.20–5.26; P = 0.01 and second stage duration (adjusted OR: 1.13; 95% [CI]: 1.00-1.29; P = 0.05) were independently associated with more severe SGH. Conclusions: The duration of second stage and ripening of the cervix during induction of labor are independently associated with SGH severity following attempted VAD.